Estudo de caso do programa Mútuo de sementes na Cooperativa Agropecuária & Industria (COTRIJUI ) - Strada, Anderson (2012)
This essay seeks to identify and analyze the different modalities of the soybean seed trade by COTRIJUI, presenting a brief characterization of the official procedures followed by the cooperative in relation to the seed sector. It deals also with the main issues concerning seed certification, seed quality, trade and commerce supervision. A study was undertaken on the seed business, relating theoretical knowledge with personal skills and facts from everyday practice. Data concerning the mutual program of soy seed trade (MSP) were collected between the years 2005 and 2011, based on the exchange of soybean seeds for industry purposes. Throughout this period the different ways adopted by the MSP were listed and discussed, considering different groups according to the productive potential of soybean cultivars, the time period during which they remain available on the market, size after undergoing sieve grading (small or large seeds) and different kinds of insecticide, fungicide and nutrient treatments, to which marketed seed is subjected. This work, conducted on the Ijui unit of COTRIJUI, revised data allowing to the assessment of the cooperative performance and its future potential. As a result, the trade system in practice proved to be feasible for both, the cooperative and the farmer who fully adhered to the system. It was observed also that it is possible to add value to products that potentiate the seed trade, which stresses the importance that must be given to this subject.